Peran One Health dalam Meningkatkan Ketahanan Komunitas terhadap Zoonosis: Tinjauan Sistematis: The Role of One Health in Enhancing Community Resilience against Zoonosis: A Systematic Review - Febriangga Harmawan; Siti Amanah; Sumardjo Sumardjo; Sarwititi Sarwoprasodjo (Journal of Health, 2026)
Background: The increasingly complex zoonotic threats and global health dynamics necessitate a comprehensive One Health approach to enhance community resilience. Despite acknowledging this framework’s relevance, previous research reveals fragmented findings and insufficient integration of crucial socio-economic dimensions in pandemic response. This systematic review aims to synthesize knowledge, identify trends, gaps, and scientific contributions surrounding the interaction between One Health and zoonosis. Objective: The main objective is to comprehensively identify trends, gaps, and contributions within the academic discourse of One Health, zoonosis, and community resilience. Methodology: Following PRISMA guidelines, a rigorous Systematic Literature Review (SLR) was conducted using the Scopus database. We included 65 relevant articles published from 2019 to 2024, focusing on One Health-zoonosis intersections and community-level interventions. Qualitative thematic synthesis was employed to integrate diverse findings and identify core patterns. Results: Findings show the scientific narrative has shifted to integrate Community Resilience as a vital component alongside One Health and Zoonosis pillars. Analysis revealed geographical polarization: developing countries focus on strengthening local capacity, while developed nations emphasize advanced technology. Highly cited literature tends toward quantitative and mixed methods approaches for greater evidence. Conclusion: This study contributes by synthesizing fragmented knowledge and integrating elements such as local knowledge, digital technology, and gender dynamics into a holistic One Health framework. The key implication is a research paradigm shift towards integrated methodologies to yield robust and actionable evidence. Policy Implication national health strategies must shift from top-down interventions to incorporating local indigenous knowledge and digital surveillance tools to ensure equitable resilience.